Bioplastic composites of Pineapple leaf fibers with biopolymer - Tiah, Chai Ching (School of Bioprocess Engineering, Universiti Malaysia Perlis, 2010)
Pineapple leaf that usually threw away has gained lots of attention from the scientists. Salvaging natural fiber has carried out time to time. This study investigates the effect on mechanical properties when pineapple leaf fibers (PALF) are reinforced with biopolymer, polylactic acid (PLA). At the same time, production of this composite is aiming to replace the non-biodegradable plastic. Pineapple leaves that collected for gratis from the post-harvest will undergo retting process for a week after compressed using the sugarcane machine. After extraction of fibers, the PALF was cut into 6-10 mm length to ensure reinforcement process run efficiently. Both short treated and untreated PALF were compounded respectively with PLA using the Z-blade mixer prior to compression molding via hot press machine to form a sheet. Formation of composite sheet indicated the starting of mechanical testing for tensile (ASTM D638), flexural (ASTM D790) and impact (ASTM D256). Scanning electron microscope (SEM) was used to scrutinize the topology and morphology of the PALF/PLA composite while thermogravimetric analyzer (TGA) determined the decomposition temperature of the composite. Outcome results showed composite was brittle but able to withstand flexure and impact strength identical to neat PLA sample. Treated PALF/PLA composite performed the best mechanical properties